Konjungtivitis Alergi - Noval Ramadirta; Mentari Putri Maharani; Rachel Agustin Inggrid Zefanya; Yashila Rahimah; Rani Himayani; Putu Ristyaning Ayu Sangging (Medula, 2023)
Allergic conjunctivitis is a form of ocular disorder associated with hypersensitivity reactions to foreign bodies. Allergic conjunctivitis is often a reaction to topical and systemic medications or cosmetics and animal dander from cats and/or dogs. Allergic conjunctivitis is a consequence of a type 1 allergic reaction. In individuals with hypersensitivity, when the allergen is present in the conjunctiva, this allergen triggers a reaction that causes Th2 cells to produce cytokines that induce the production of immunoglobulin E (IgE) by B cells. Classification of allergic conjunctivitis based on Ocular Allergy from the European Academy of Allergy and Clinical Immunology (EAACI) are ocular surface hypersensitivity disorders including ocular allergy or non-allergic ocular hypersensitivity. The diagnosis and management of this disease are related to the clinical manifestations that occur in patients. General management in the form of avoiding allergens and improving eye hygiene must be considered so that chronicity does not occur in the disease and interferes with the patient's quality of life. Some cases of allergic conjunctivitis do not pose a severe health threat. Complications of allergic conjunctivitis are rare, but when they do, they can be serious, including, in severe cases, scarring of the eye. If allergic conjunctivitis develops into infective conjunctivitis, the infection can spread to other body areas, potentially causing severe secondary infections. This article will provide a deeper understanding of allergic conjunctivitis, its diagnosis and management.